1996
DOI: 10.1152/ajpcell.1996.271.6.c1887
|View full text |Cite
|
Sign up to set email alerts
|

CFTR-dependent membrane insertion is linked to stimulation of the CFTR chloride conductance

Abstract: We examined the relation between Cl current (Icl) stimulation and cell membrane capacitance (Cm) when cystic fibrosis transmembrane conductance regulator (CFTR) was expressed in Xenopus oocytes. ICl and Cm increased in parallel when oocytes expressing CFTR were stimulated by forskolin (10 microM) and 3-isobutyl-1-methylxanthine (1 mM). The adenosine 3',5'-cyclic monophosphate (cAMP)-induced increase in surface area detected by Cm was confirmed by morphometry in the same oocytes used for the electrical recordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 18 publications
7
81
2
Order By: Relevance
“…In relation to the initial rationale for these studies, we monitored ⌬C m because Csp is known to function in regulated exocytosis in other systems (21). Control oocytes not injected with CFTR cRNA showed no changes in I m or C m in response to cAMP stimulation, as observed previously (41). Expression of Csp without CFTR also yielded no I m or C m responses to cAMP (data not shown).…”
Section: Csp Interacts With the R-domain And N Terminus Of Cftr-supporting
confidence: 85%
See 2 more Smart Citations
“…In relation to the initial rationale for these studies, we monitored ⌬C m because Csp is known to function in regulated exocytosis in other systems (21). Control oocytes not injected with CFTR cRNA showed no changes in I m or C m in response to cAMP stimulation, as observed previously (41). Expression of Csp without CFTR also yielded no I m or C m responses to cAMP (data not shown).…”
Section: Csp Interacts With the R-domain And N Terminus Of Cftr-supporting
confidence: 85%
“…The quality of synthesized cRNA was determined by spectrophotometry and agarose gel electrophoresis. Oocyte preparation and cRNA injections were carried out as described by Takahashi et al (41). Expression proceeded for 2-6 days before current and capacitance recordings, which were performed as described (10,41).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus possible that both CFTR and F508del-CFTR lie mostly in the subapical region and that, upon stimulation (eg, by cAMP) CFTR, but not F508del-CFTR, undergoes exocytosis to the apical membrane, as first suggested by Bradbury et al (1992) and also by other authors (Biwersi et al, 1996;Prince et al, 1994;Takahashi et al, 1996;Tousson et al, 1996). The fact that a number of other studies reported apparently contradictory observations (Dho et al, 1993;Dunn et al, 1994;Hug et al, 1997), provides evidence that the issue of CFTR and vesicular trafficking is still an open Double labeling of CFTR, calnexin, p58, and tubulin.…”
Section: Penque Et Almentioning
confidence: 81%
“…Cell surface biotinylation indicates that CFTR undergoes rapid and efficient internalization in both polarized epithelial and nonpolarized cells (9,10). In addition, several studies indicate that the distribution of CFTR may be regulated by PKA by promoting the translocation of CFTR from an intracellular pool to the plasma membrane and by inhibiting the internalization of CFTR from the plasma membrane (43)(44)(45)(46)(47). These results suggest that the amount of CFTR in the plasma membrane may be regulated by insertion and retrieval mechanisms and that these processes may provide a mechanism to augment PKA activation in regulating CFTR in the plasma membrane.…”
Section: Inducible Overexpression Of Dominant-negative 2 Inhibits Thementioning
confidence: 99%